The Effect Of Provision Of Extraction Of Berenuk Fruit (Crescentia Cujete Linn) On Postpartum Mothers With Constipation At Mandala Public Health Care 2022 - Nani Yuningsih; Siti Rusyanti (Institute Of Computer Science (IOCS), 2023)
There are about 38% of postpartum mothers who are afraid and have difficulty during defecation. Management of postpartum mothers be able to be pharmacologically, administering drugs via rectal or taken orally, having pharmacological or non-pharmacological effects on nutritional intake, early mobilization. Provision of complementary therapy based on local wisdom, namely Berenuk fruit (Crescentia Cujete L.) as a drug to treat constipation or constipation can be a safe solution. in the working area of Mandala Public Health Care Rangkasbitung in 2022. Quasi experimental research design with Control Group Posttest-Only design. The samples in this study were 34 people, 17 intervention groups were given beenuk fruit extract at a dose of 23.53 mg once given healthy food and control group 17 people with healthy food, August – September 2022. Postpartum inclusion criteria with constipation on 3-4 days. Univariate data analysis of the age of the intervention and control groups had the same average age of 18 young and 38 years old, the average parity of the different control groups was parity 3 and intervention parity 5. Bivariate analysis of berenuk fruit extract containing anthraquinone as a laxative dose of 23.53 mg had a speed of 13.4 times faster for defecation to occur with a span of less than 2 hours when compared to the post partum mother group who were constipated and only given healthy food for more than 15 hours with the bivariate test the p value = 0.000 (p < ), which means that there was a very significant difference in the mean occurrence of defecation between the two groups (the group of post partum mothers who were given berenuk fruit extract and the group of post partum mothers who were only given healthy food). Using the Mann Whitney statistical test, It is hoped that local wisdom can be applied in midwifery services to postpartum mothers in fulfilling the physiological needs of elimination with constipation during the puerperium.